WAYS OF USING ANALYTICAL PROCEDURES IN ASSESSING THE RELIABILITY OF INFORMATION ABOUT LIABILITIES - Ochilov Farxodjon Shavkatjon ugli (Research Parks Publishers, 2023)
The use of international standards in auditing procedures leads to an increase in the quality of auditing. In order to increase the quality of the audit, it is necessary to pay attention to its methodological aspects, in particular, the wide use of analytical procedures during the audit process. This article describes the directions of applying analytical procedures in the audit of liabilities. As a result of the research, proposals were developed to improve the process of applying analytical procedures in the performance audit.